Efficacy of carbocisteine in the treatment of chronic obstructive pulmonary disease and impact on the quality of life - Esad Alibašić; Amira Skopljak; Aida Čengić; Gorana Krstović; Nataša Trifunović; Tarik Čatić; Belma Kapo; Meliha Mehić; Amila Hadžimuratović (Medicinski glasnik, 2017)
Aim: To investigate the effects of carbocisteine treatment in the reduction of frequency of productive cough episodes, preventing disease progression and improving the quality of life as well as the tolerability of the administered treatment and patient compliance during the study. Methods: This observational, non-interventional, multicenter, cohort study included 501 patients with chronic obstructive pulmonary disease (COPD) who were administrated carbocisteine capsules 375 mg and followed up during the next 15 days. The patients were observed at 3 points, baseline and two additional assessments. General clinical condition of patients, along with the spirometry testing at all three points were examined. Thr quality of life was assessed on the 1st and 3rd observation with Leicester Cough Questionnaire. Tolerability and patient compliance were measured throughout the study. Results: There was a significant change of forced expiratory volume in 1 second (FEV1) status between the second and third observation (p=0.002). Examination of general symptoms showed a statistically significant reduction in cough by 74.9%, in sputum production by 48.5%, in dyspnea by 29% and in fatigue by 50%. After the administration of carbocisteine the median value of overall quality of life was 3.79 (3.63-3.89). Conclusion: 375mg carbocisteine capsules were found to be effective and well-tolerated in the treatment of COPD, with a small percentage of reported mild adverse reactions and with a significant improvement of quality of life.
Keywords: lung disease; cough; expectorants